Digitalization in Organizations. - Çögenli, Mehmed Zahid (Cambridge Scholars Publisher, 2021)
This volume carries out an evaluation of the digital transformation process for organizations, which has accelerated further with the influence of COVID-19. It provides an up-to-date perspective by addressing organizational aspects and activities of different fields in the social sciences. The contributions gathered here discuss the digital transformation of social and organizational studies related to disciplines such as public practices, human resource management, finance, education, occupational health and safety, organizational behavior, health management, management strategies, entreprene.